PEMIKIRAN POLITIK-EKONOMI PRIODE AL-KHULAFA AL-RASYIDIN (TELAAH KAJIAN POLITIK DAN EKONOMI DALAM PERSPEKTIF SEJARAH) - Hartono, Hartono; Prasetyo, Totok Adhi (At-Tawazun, Jurnal Ekonomi Syariah, 2024)
Al-Khulafa Al-Rasyidin, or what is known as the four caliphs who succeeded the Prophet Muhammad, namely Abu Bakr, Umar bin Khatab, Uthman bin Affan, and Ali bin Abi Talib, in the history of Islamic development and thought had a quite significant role in the development of Islam, so that many experts Historians, economists, and political thinkers quote several concepts that were carried out by one of the existing caliphs. This research uses a library study method, where researchers collect data from various sources, including books, journals, and articles. Then, it is analyzed to obtain comprehensive conclusions. The research results found that of the four Rasyidin Khulafaur, the first, Abu Bakr, who ruled for only about 27 months during his leadership, dealt with a lot of problems with apostasy and people who refused to pay zakat. Second, during the time of Umar Ibn Khatab, Baitul Mall was established, paying zakat, usrh (tax payment), and sadaqah for non-Muslim Banu Taghlib Christians. Third, Uthman Bin Affan, in his economic policies was too naive to be called that because he was a very rich man and then saved his money combined with the state treasury in the end. It gave rise to misunderstandings between him and the head of the Central Baitul Mall, from this incident, a controversial conflict arose between personal salary and personal expenses. Fourth, during the time of Ali Bin Abi Tholib, the strengthening of Baitul Mall was strengthened with an equal approach to all Muslims.